Mango (Mangifera indica L.) kernel fat : fatty acid profile, oxidative stability and development of fourier transform near infrared (FT-NIR) spectroscopy calibration models - Schoeman, Mathilda Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc )--Stellenbosch University, 2002.